TFE3 Regulates the Function of the Autophagy-Lysosome Pathway to Drive the Invasion and Metastasis of Papillary Thyroid Carcinoma. (7th October 2021) - Lu, Hongsheng; Zhu, Chumeng; Ruan, Yanyun; Fan, Lilong; Wei, Kena; Yang, Zhaohui; Chen, Qi
Abstract : Background . Accumulating evidence shows that autophagy plays a vital role in tumor occurrence, development, and metastasis and even determines tumor prognosis. However, little is known about its role in papillary thyroid carcinoma (PTC) or the potentially oncogenic role of TFE3 in regulating the autophagy-lysosome system. Methods . Immunohistochemistry and quantitative real-time PCR (qRT-PCR) were used to examine the expression of TFE3, P62/SQSTM1, and LC3 in PTC and paracancerous tissues. TFE3, P62/SQSTM1, LC3, cathepsin L (CTSL), and cathepsin B (CTSB) were evaluated using Western blot analysis. After inducing TFE3 overexpression by plasmid or TFE3 downregulation by small interfering RNA (siRNA) transfection, MTT, wound healing, and cell migration and invasion assays were used to verify the effects on invasion, migration, and the levels of autophagy-lysosome system-related proteins such as P62/SQSTM1, LC3, CTSL, and CTSB. Results . TFE3 was overexpressed in PTC tissues compared with paracancerous tissues. Analysis of the clinicopathological characteristics of PTC patients showed that high TFE3 expression was significantly correlated with lymph node metastasis. TFE3 overexpression in the PTC cell lines KTC-1 and BCPAP promoted proliferation, invasion, and migration, while TFE3 knockdown had the opposite effects. Furthermore, we identified a positive relationship among the expression levels of TFE3, P62/SQSTM1, LC3, CTSL, and CTSB. We found that silencing TFE3 inhibited the expression of P62/SQSTM1, LC3, CTSL, and CTSB in PTC cells. However, TFE3 overexpression had the opposite effects. Conclusions . The present study provided evidence for the underlying mechanisms by which TFE3 induces autophagy-lysosome system activity in PTC.